1996
DOI: 10.1016/s0924-9338(97)81055-3
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis, mind, and mirth

Abstract: In the context of the discovery of the cerebral ligand for the cannabis receptor, and the elucidation of its genetic sequence, we discuss the psychomimetic properties of Cannabis sativa, and explore the relationship between cannabis intoxication and mood. We suggest that renewed study of acute cannabis encephalopathy would be rewarding not only in deepening our understanding of consciousness in healthy adults, but also in helping us to understand the perceptual world of the child, the elderly, and some of our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Experimental work in humans has demonstrated that the acute effects of cannabis (intoxication) include psychotic symptoms, mood changes and cognitive impairment in both normal subjects (60–62) and patients with schizophrenia (60, 63). Because of shared neural circuitries involved in the pathophysiology of both CP and schizophrenia, where endogenous cannabinoids could play a significant role (5), there are certain similarities in their symptomatology (64, 65), but also some differences, such as those observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental work in humans has demonstrated that the acute effects of cannabis (intoxication) include psychotic symptoms, mood changes and cognitive impairment in both normal subjects (60–62) and patients with schizophrenia (60, 63). Because of shared neural circuitries involved in the pathophysiology of both CP and schizophrenia, where endogenous cannabinoids could play a significant role (5), there are certain similarities in their symptomatology (64, 65), but also some differences, such as those observed in the present study.…”
Section: Discussionmentioning
confidence: 99%